Comparison of Fluid Analysis and Cytologic Findings of Cerebrospinal Fluid Between Three Collection Sites in Adult Equids With Neurological Disease - Young, Kimberly A. S.; Hepworth-Warren, Kate L.; Dembek, Katarzyna A. (Frontiers in Veterinary Science, 2022)
Cerebrospinal fluid (CSF) is routinely collected from three sites in the horse, the atlanto-occipital (AO), atlantoaxial (AA), and lumbosacral (LS) space. A comparison between fluid analysis parameters [total protein, total nucleated cell count (TNCC), red blood cell (RBC) count, and morphologic analysis] from samples obtained at each of the three sites has not previously been performed. A retrospective analysis was performed to evaluate the differences in fluid analysis of CSF between the AO, AA, and LS sites in equids presented to a referral service for evaluation of suspected neurological disease. A total of 113 equids aged ≥1 year that underwent CSF collection between 2008 and 2020 were included. Total nucleated cell count, RBC concentration, total protein (TP), and morphologic evaluation between CSF samples obtained from the three sites were compared. When comparing all samples, LS centesis was associated with higher RBC compared to other sites (p < 0.05); TP was lower in the AA group than in the LS group (p < 0.05). Within a subset of cytologically unremarkable samples, RBC concentration was highest in LS samples (p < 0.01); TP was higher in LS samples compared to AA samples (p < 0.05) and TNCC was higher (p < 0.01) in AA and LS groups compared to the AO. In cytologically abnormal samples, there were no significant differences between sites in any parameter. Abnormal cytology was correlated with non-survival (p = 0.0002). Non-survival was associated with higher TNCC (p < 0.01). The receiver operating characteristic (ROC) curve for TNCC had an area under the curve of 0.67 (95% CI, 0.55–0.79) and indicated that a cutoff value of 24 cells/μL maximized specificity (72%) and sensitivity (54%) to predict non-survival in all horses. Positive predictive value was 45%; negative predictive value was 78%. The concentration of RBC was higher in samples from the LS site. This has clinical implications due to the importance of comparative diagnostics and its potential impact on cytologic evaluation. There were minimal differences in multiple other parameters between sites, which are likely clinically insignificant.